Horse vocabulary in Uzbek and Russian languages - Yusupova Barchinoy Qaxramanovna (Research Parks Publishing LLC, 2020)
In each language, words are grouped according to their characteristics. it is more difficult to classify words in Uzbek by categories than in Russian, because, as mentioned in the previous sections, Uzbek words belonging to different categories do not have the same specific morphological features as in Russian